2017
DOI: 10.1096/fj.201700480r
|View full text |Cite
|
Sign up to set email alerts
|

Normoxic cells remotely regulate the acid‐base balance of cells at the hypoxic core of connexin‐coupled tumor growths

Abstract: ATP fuels the removal of metabolic end-products, including H ions that profoundly modulate biological activities. Energetic resources in hypoxic tumor regions are constrained by low-yielding glycolysis, and any means of reducing the cost of acid extrusion, without compromising pH homeostasis, would therefore be advantageous for cancer cells. Some cancers express connexin channels that allow solute exchange between cells, and we propose that, this route, normoxic cells supply hypoxic neighbors with acid-neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Such coupling would result in syncytial behaviors of clusters of cells, but the relevance of this to cancer is likely to be limited to special cases, because gap junctional coupling tends to be low or absent in tumors [70], possibly due to the tumor-suppressing effect that has been attributed to connexins [71,72]. Nonetheless, there are cases of well-coupled cancer cells, and in such instances, pH regulation would operate in a syncytial mode [73,74]. Some key points borne from the analyses presented herein are paraphrased below:…”
Section: Discussionmentioning
confidence: 99%
“…Such coupling would result in syncytial behaviors of clusters of cells, but the relevance of this to cancer is likely to be limited to special cases, because gap junctional coupling tends to be low or absent in tumors [70], possibly due to the tumor-suppressing effect that has been attributed to connexins [71,72]. Nonetheless, there are cases of well-coupled cancer cells, and in such instances, pH regulation would operate in a syncytial mode [73,74]. Some key points borne from the analyses presented herein are paraphrased below:…”
Section: Discussionmentioning
confidence: 99%
“…Additional reports also indicate that hypoxia modulates Cx43 and GJIC in other cancer types. For example, it has been shown that hypoxia induces Cx43 expression and GJIC in pancreatic ductal adenocarcinoma cells, promoting tumor progression by different metabolic cell coupling-mediated mechanisms [ 55 , 56 ]. We have previously identified that the pre-incubation of melanoma cells to hypoxic conditions, decreases their susceptibility to NK cell cytotoxic attack by interfering with Cx43-GJICs via autophagy-mediated Cx43 degradation at the cytotoxic immunological synapse [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 ) ions to balance their proton surplus in the hypoxic centerpiece of tumor growth via the so-called connexin (gap-junction protein) -composited "communicating" transitions (142)(143)(144).…”
Section: The Influence Of Tumor Microenvironment On Early Malignancymentioning
confidence: 99%